2003
DOI: 10.1128/jcm.41.7.3013-3016.2003
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Nucleic Acid Amplification Methods for Detection of Chlamydia trachomatis in Urine: Results of the First International Collaborative Quality Control Study among 96 Laboratories

Abstract: The first European Quality Control Concerted Action study was organized to assess the ability of laboratories to detect Chlamydia trachomatis in a panel of urine samples by nucleic acid amplification tests (NATs). The panel consisted of lyophilized urine samples, including three negative, two strongly positive, and five weakly positive samples. Ninety-six laboratories in 22 countries participated with a total of 102 data sets. Of 204 strongly positive samples 199 (97.5%) were correctly reported, and of 506 wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 17 publications
0
29
1
1
Order By: Relevance
“…A further EQA study of detection of C. trachomatis in urine samples, based in Australia, found varying performance depending on the concentration (0 to 100%) and reported that low-level positives could not be detected consistently by a single test (18). In contrast to the results reported by Verkooyen et al (26), Land et al (18) found that at lower concentrations of C. trachomatis, the Roche AMPLICOR CT/NG assay was more sensitive than the Abbott LCx. However, Goessens et al (14) examined the detection of C. trachomatis in female specimens (urine and swabs) and found no difference among three commercial tests (Abbott LCx, GenProbe AMP-CT, and Roche COBAS AMPLICOR CT/NG).…”
contrasting
confidence: 49%
See 2 more Smart Citations
“…A further EQA study of detection of C. trachomatis in urine samples, based in Australia, found varying performance depending on the concentration (0 to 100%) and reported that low-level positives could not be detected consistently by a single test (18). In contrast to the results reported by Verkooyen et al (26), Land et al (18) found that at lower concentrations of C. trachomatis, the Roche AMPLICOR CT/NG assay was more sensitive than the Abbott LCx. However, Goessens et al (14) examined the detection of C. trachomatis in female specimens (urine and swabs) and found no difference among three commercial tests (Abbott LCx, GenProbe AMP-CT, and Roche COBAS AMPLICOR CT/NG).…”
contrasting
confidence: 49%
“…Nonetheless, EQA provides valuable insight into the standard of clinical diagnostic testing by laboratories. In addition to monitoring standards, the process of EQA collates information that can be utilized to provide insight into the performance of specific laboratory methods (18,26). In this study, EQA enabled the comparison of C. trachomatis detection by differing assay types (EIA and NAAT) and also the comparison of the three main NAAT used by participants in the study (Abbott LCx, BDProbeTecET, and the Roche AMPLICOR/COBAS CT/NG method group), with two distinct sources of C. trachomatis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Freeze-drying has previously been shown to be a suitable method for preserving DNA in various matrixes (Huckenbeck and Bonte, 1992;Verkooyen et al, 2003) and was thus chosen as the preservation method. Efficient lysis of the cells were ensured by treating the freeze-dried cocoa pulp enzymatically with protinase K and lysozyme, chemically with SDS, and mechanically by freeze-thaw cycles and bead beating.…”
Section: Development Of a Dgge Protocol For The Study Of Yeast Populamentioning
confidence: 99%
“…Key to the success of these laboratory networks is the use of standardized procedures and assays in all of the associated laboratories, which in turn is reliant on specific training programs as well as a demonstrated proficiency of laboratory workers to perform the assays in question. For molecular biology-based assays, evaluations of proficiency test practices have identified analytic errors associated with all stages of the testing process as well as errors specific to the physical setup of individual laboratories, emphasizing the need for on-site proficiency testing (2,3,11,15,16). There are, however, biosecurity risks associated with the distribution of live agents for training or proficiency test purposes, as documented by the inadvertent global distribution of a pandemic strain of influenza A/H2N2 virus in a public health laboratory proficiency panel during early 2005.…”
mentioning
confidence: 99%